Double aneuploidy with Edwards-Klinefelter syndromes (48,XXY,+18) of maternal origin: Prenatal diagnosis and molecular cytogenetic characterization in a fetus with arthrogryposis of the left wrist and aplasia of the left thumb - Chih-Ping Chen; Schu-Rern Chern; Chen-Yu Chen; Pei-Chen Wu; Li-Feng Chen; Chen-Wen Pan; Wayseen Wang (Elsevier, 2011)
Objective: To present the prenatal diagnosis and molecular investigation of the parental origin and mechanism of nondisjunction underlying an 48,XXY,+18 karyotype in a fetus with congenital abnormalities, and to review the literature. Materials, Methods, and Results: A 42-year-old woman was referred for amniocentesis at 18 weeks of gestation because of advanced maternal age. Prenatal ultrasound revealed bilateral choroid plexus cysts. Amniocentesis revealed a karyotype of 48,XXY,+18. The parental karyotypes were normal. Level II ultrasound revealed a flexion contracture deformity of the left wrist with absence of the thumb. The pregnancy was terminated at 22 weeks of gestation. A 332 g male fetus was delivered with clenched hands, arthrogryposis of the left wrist, aplasia of the left thumb, micrognathia, low-set ears, hypertelorism, rocker-bottom feet, and a normal penis. Quantitative fluorescent polymerase chain reaction assays using polymorphic DNA markers showed a triallelic pattern with a dosage ratio of 1:1:1 (paternal:maternal:maternal) for chromosome 18-specific markers, and a monoallelic pattern of a single maternal allele for chromosome X-specific markers. The fetus inherited two copies of two different maternal alleles on chromosome 18, and two copies of a single maternal allele on chromosome X. The molecular result, along with the karyotype of 48,XXY,+18, was consistent with the occurrence of nondisjunction of chromosome 18 in a maternal meiosis I error and nondisjunction of chromosome X in a maternal meiosis II error or less likely a postzygotic mitotic error. Conclusion: The present case provides evidence that abnormal separation of chromosomes 18 and X resulting in double aneuploidy may occur in different cell divisions, and such an occurrence is related to advanced maternal age.